2012
DOI: 10.1177/0042085912446033
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Teacher Efficacy Beliefs in Promoting Resilience to Support of Latino Students

Abstract: This article explores the connection of teacher self-efficacy beliefs in promoting student resilience to teaching practice and support of Latino students. Results suggest that efficacy beliefs related to resilience are linked to building important relationships through connecting with students, building on their experiences and knowledge, and understanding the issues they confront. In particular, important to strengthening the academic resilience of Latino students are teachers' views of their use of Spanish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 67 publications
3
35
0
Order By: Relevance
“…The effect size of predicting accuracy was moderate due to self-efficacy but smaller due to self-efficacy and subjective wellbeing. The result of this study also supported studies' findings in the past such as Sosa and Gomez (2012) and Hong (2012), indicating the positive effect of self-efficacy on resilience.…”
Section: Discussionsupporting
confidence: 89%
“…The effect size of predicting accuracy was moderate due to self-efficacy but smaller due to self-efficacy and subjective wellbeing. The result of this study also supported studies' findings in the past such as Sosa and Gomez (2012) and Hong (2012), indicating the positive effect of self-efficacy on resilience.…”
Section: Discussionsupporting
confidence: 89%
“…By recognizing the challenges that students of diverse cultures face, and by responding with accurate strategies, school leaders can build bridges with the community to break the barriers that currently obstruct students' academic achievement (Sosa and Gomez 2012).…”
Section: Limitations On Leadershipmentioning
confidence: 99%
“…Studies of minority immigrant students' perceptions of teachers reveal that students are aware of efforts from teachers to reach out to them (Erickson 1987;Ozer, Wolf, and Kong 2008;Phelan, Davidson, and Cao 1991;Warikoo 2004). For example, Sosa and Gomez (2012) find in their qualitative study of a large urban high school that students notice when teachers are sensitive to the life experiences as working class Mexican-American students. In contrast to studies that reveal strong relationships between students and teachers, other work has shown that some student-teacher relationships can be less positive (Lee 2005;Louie 2012;Rosenbloom and Way 2004).…”
Section: Minority Immigrant Youth and Their Teachersmentioning
confidence: 99%